Elimination of refractory ventricular tachycardia storm and fibrillation using stereotactic radiotherapy - Alexander Wutzler; Borris Tiedke; Mohamed Osman; Noha Mahrous; Reinhard Wurm (Clinical Case Reports, 2023)
Abstract Ventricular tachycardia storm is a potentially lethal condition with limited treatment options. Failed ablation is associated with a fourfold mortality increase in this population. Stereotactic body radiotherapy was proposed in these cases. We report a case where radiotherapy was safely performed, leading to the elimination of adequate shocks.